Nitrogen-fixing bacteria and nitrogen fertilization on economic feasibility of tomato (2022)
To increase the availability of nutrients and improve crop productivity, chemical fertilizers are introduced to the soil, although the biological fixation of nitrogen contributes globally with 180 million metric tons of ammonia per year, which is comparable to current contribution of anthropogenic nitrogen. In this way, the present study aimed to evaluate the effect of the interaction of Azospyrillum brasilense and Bradyrhizobium japonicum with different levels of nitrogen on the yield and economic viability of the tomato crop. An experimental design of divided plots was used, with the nitrogen fertilization dose being the largest plot (100% of the dose, 50% of the dose and 0% of the dose) and the minor plot of nitrogen-fixing bacteria (100 cc ha-1, 200 cc ha-1, 300 cc ha-1) with four random internal blocks and five plants as experimental unit. The variables evaluated were: production per plant, yield/ha, number of fruits/plant and average fruit weight. Finally, the economic analysis was performed according to the combination of the treatments. The results obtained showed that the mixture of nitrogen-fixing bacteria (BFN) (Azospyrillum brasilense and Bradyrhizobium japonicum) at a dose of 100 cc ha-1, significantly increased tomato production when nitrogen (urea) was not applied. The application of BFN in combination with adequate levels of nitrogen favors the sustainability of the tomato.